Inventarisasi Gulma Daun Lebar di Pertanaman Cengkeh pada Fase Tanaman Belum Menghasilkan di Desa Ariate, Kabupaten Seram Bagian Barat - Tanasale, Vilma Laurien; Makaruku, Marlta H; Goo, Nureny; Wattimena, Anna (JURNAL PERTANIAN KEPULAUAN, 2023)
Indonesia has a very high diversity of ecosystems ranging from land areas to the ocean, includingsmall islands in Maluku Province. The diversity of plant species on small islands is stronglyinfluenced by local habitats and climates. The Maluku region has site-specific crops such as clovesand nutmeg that are cultivated by most farmers. But in reality, there has been a continuous declinein production and one of the causes is the presence of weeds. The objective study is to identify thetypes of weeds and SDR values in the clove planting area in Ariate Village, West Seram Regency.The survey method is used to collect data directly in the field. In conducting vegetation analysis, thepurposive quadratic method is used. Data collected in the form of primary data and secondary dataThis study used a sample plot measuring 1 x 1 m. The results showed the presence of 10 types ofbroadleaf weeds, from 6 families in this village. The dominant weed in the clove planting area at thestage of immature plants is Clidemia hirta weed with an SDR value of 57,574%